The Impact of Government Expenditure and Sectoral Investment on Economic Growth in South Africa - MEYER, Daniel Francois; MANETE, Tebogo; MUZINDUTSI, Paul Francois (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
Globally, but especially in developing countries, economic growth has been low since the financial crises in 2008/2009. Among the key factors that can stimulate growth are government spending and capital investments. The purpose of the study was to examine the effect of government expenditure and sectoral investment on economic growth in South Africa. Econometric methods including a VAR model were used to analyze the impact of government spending and investment in economic sectors on economic growth. This study used quarterly time series data from 1995 to 2016.Selected economic sectors were mining, manufacturing and financial sectors. The results of the Vector error correction model (VECM) indicated that in the short run only investment in the financial sector has a significant effect on economic growth in South Africa. However, the long-run results showed that only investment in manufacturing sector had a positive effect on economic growth, while the effect of government spending on economic growth was found to be minimal. It is proposed that more investment be attracted and directed towards economic sectors rather than on government spending.